DICOM re‐encoding of volumetrically annotated Lung Imaging Database Consortium (LIDC) nodules. Issue 11 (6th September 2020) - Fedorov, Andrey; Hancock, Matthew; Clunie, David; Brochhausen, Mathias; Bona, Jonathan; Kirby, Justin; Freymann, John; Pieper, Steve; J. W. L. Aerts, Hugo; Kikinis, Ron; Prior, Fred
Abstract : Purpose: The dataset contains annotations for lung nodules collected by the Lung Imaging Data Consortium and Image Database Resource Initiative (LIDC) stored as standard DICOM objects. The annotations accompany a collection of computed tomography (CT) scans for over 1000 subjects annotated by multiple expert readers, and correspond to "nodules ≥ 3 mm", defined as any lesion considered to be a nodule with greatest in‐plane dimension in the range 3–30 mm regardless of presumed histology. The present dataset aims to simplify reuse of the data with the readily available tools, and is targeted towards researchers interested in the analysis of lung CT images. Acquisition and validation methods: Open source tools were utilized to parse the project‐specific XML representation of LIDC‐IDRI annotations and save the result as standard DICOM objects. Validation procedures focused on establishing compliance of the resulting objects with the standard, consistency of the data between the DICOM and project‐specific representation, and evaluating interoperability with the existing tools. Data format and usage notes: The dataset utilizes DICOM Segmentation objects for storing annotations of the lung nodules, and DICOM Structured Reporting objects for communicating qualitative evaluations (nine attributes) and quantitative measurements (three attributes) associated with the nodules. The total of 875 subjects contain 6859 nodule annotations. Clustering of the neighboring annotations resulted in 2651 distinct nodules. The data are available in TCIA at https://doi.org/10.7937/TCIA.2018.h7umfurq . Potential applications: The standardized dataset maintains the content of the original contribution of the LIDC‐IDRI consortium, and should be helpful in developing automated tools for characterization of lung lesions and image phenotyping. In addition to those properties, the representation of the present dataset makes it more FAIR (Findable, Accessible, Interoperable, Reusable) for the research community, and enables its integration with other standardized data collections.